Analysis of The Use of Mastery Learning Models on The Learning Outcomes of Students' Akidah Akhlak At Mts Mambaul Ulum Simorejo Widang Tuban - Suwaibatul Aslamiyah; Berliana (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2023)
This study entitled Analysis of the Use of the Mastery Learning Learning Model on the Learning Outcomes of the Aqidah Akhlak Students at MTS Mabaul Ulum Simorejo Widang Tuban uses quantitative and associative approaches. The purpose of this research is to determine the use of the learning model Mastery Learning at MTS Mambaul Ulum Simorejo Widang Tuban, which is classified as very good at 87.89%, which is between the interval values ​​of 76-100%, to find out the Aqidah Akhlak Learning Results MTs Mambaul Ulum Simorejo Widang Tuban is classified as good at 85.58 which is between the value intervals of 75% -89%, as well as knowing there is the effect of using the Mastery Learning learning model on learning outcomes Aqidah Akhlak MTs Mambaul Ulum Simorejo Widang Tuban the results of calculations with a simple linear regression formula using the SPSS application are proven by the calculation results of a significant value of 0.000 which means based on the magnitude of the correlation/relationship with a value of 0.899 when seen from the interpretation table between 0.80-1.000 indicates that between variables X and Y, there is a very strong relationship